Synergistic Activity and Mechanism of Sanguinarine with Polymyxin B against Gram-Negative Bacterial Infections - Luyao Qiao; Yu Zhang; Ying Chen; Xiangyin Chi; Jinwen Ding; Hongjuan Zhang; Yanxing Han; Bo Zhang; Jiandong Jiang; Yuan Lin (MDPI AG, 2024)
Compounds that potentiate the activity of clinically available antibiotics provide a complementary solution, except for developing novel antibiotics for the rapid emergence of multidrug-resistant Gram-negative bacteria (GNB). We sought to identify compounds potentiating polymyxin B (PMB), a traditional drug that has been revived as the last line for treating life-threatening GNB infections, thus reducing its nephrotoxicity and heterogeneous resistance in clinical use. In this study, we found a natural product, sanguinarine (SA), which potentiated the efficacy of PMB against GNB infections. The synergistic effect of SA with PMB was evaluated using a checkerboard assay and time-kill curves in vivo and the murine peritonitis model induced by Escherichia coli in female CD-1 mice in vivo. SA assisted PMB in accelerating the reduction in bacterial loads both in vitro and in vivo, improving the inflammatory responses and survival rate of infected animals. The subsequent detection of the intracellular ATP levels, membrane potential, and membrane integrity indicated that SA enhanced the bacterial-membrane-breaking capacity of PMB. A metabolomic analysis showed that the inhibition of energy metabolism, interference with nucleic acid biosynthesis, and the blocking of L-Ara4N-related PMB resistance may also contribute to the synergistic effect. This study is the first to reveal the synergistic activity and mechanism of SA with PMB, which highlights further insights into anti-GNB drug development.